2009
DOI: 10.1089/ten.tea.2008.0263
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Collagen Scaffolds for Heart Valve Tissue Engineering

Abstract: Scaffolds for heart valve tissue engineering must function immediately after implantation but also need to tolerate cell infiltration and gradual remodeling. We hypothesized that moderately cross-linked collagen scaffolds would fulfill these requirements. To test our hypothesis, scaffolds prepared from decellularized porcine pericardium were treated with penta-galloyl glucose (PGG), a collagen-binding polyphenol, and tested for biodegradation, biaxial mechanical properties, and in vivo biocompatibility. For co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 40 publications
5
111
0
2
Order By: Relevance
“…This study and others 26,38 showed that immersion is effective for tissues that are thin or relatively more porous than the aorta, which contains numerous layers of elastic fibers that restrict penetration of fluids. In some applications, immersion decellularization techniques are replaced with perfusion techniques for tissues that are difficult to decellularize.…”
Section: Novel System For Perfusion Decellularizationmentioning
confidence: 56%
See 1 more Smart Citation
“…This study and others 26,38 showed that immersion is effective for tissues that are thin or relatively more porous than the aorta, which contains numerous layers of elastic fibers that restrict penetration of fluids. In some applications, immersion decellularization techniques are replaced with perfusion techniques for tissues that are difficult to decellularize.…”
Section: Novel System For Perfusion Decellularizationmentioning
confidence: 56%
“…21 Other experimental approaches to building tissueengineered valves include use of cell-seeded biodegradable polymers (synthetic or fibrin-based, molded in the shape of an aortic valve root) to generate a homogeneous, isotropic collagenous structure lacking elastic fibers, before implantation, 22,23 implantation of stent-mounted acellular valves seeded with vascular fibroblasts or stem cells, 24 as well as use of polymers 22,25 and layered composites. 13,14,26 Creating structures as heterogeneous as that of the aortic roots using a bottom-up approach (such as three-dimensional printing 27 ) is quite difficult and requires major technological advances. Taken together, none of the above referenced approaches satisfied the design criteria.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro biodegradation of decellularized lung scaffold by 0.2% concentration of collagenase was used as an 'accelerated model' of degradation and the collagenase activities in vivo are not expected to be as harsh as in vitro [72]. Moreover, the degradation rates of the scaffold can be controlled by varying the enzyme concentrations [73] or by using various crosslinking agents (carbodiimide, glutaraldehyde), which might affect the collagen structure of the scaffold and modify the cleavage sites for collagenase enzyme [60,74,75].…”
Section: In Vitro Biodegradation Of Decellularized Goat-lung Matrixmentioning
confidence: 99%
“…To stabilize the valve extracellular matrix, the acellular roots were treated with sterile 0.1% penta galloyl glucose (PGG) in 20% isopropanol, an elastin-binding polyphenol (10) followed by a rapid glutaraldehyde treatment and complete neutralization with glycine to stabilize collagen (17). Acellular bovine pericardium, also stabilized with PGG, and used for mounting the valves within the conduit, was prepared as described before (18).…”
Section: Acellular Scaffoldsmentioning
confidence: 99%
“…Treatment with PGG, a non-cytotoxic collagen and elastin binding polyphenol reduces susceptibility to collagenase, thus increasing the durability of matrix scaffolds upon implantation (7,15,18,22). In an attempt to re-cellularize the aortic roots, we isolated sheep ADSCs and seeded them into each of the three cusps by a single injection.…”
Section: Rationale and Hypothesismentioning
confidence: 99%